2007
DOI: 10.1021/jf0709653
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Formation and Stability of Hydroxyalkylsulfonic Acids in Wines

Abstract: The presence of carbonyl compounds (CCs) in wines has sparked the interest of researchers in several countries. The quantification of some of these compounds has been used as a parameter of quality for many fermented beverages. Although present in minute quantities (except for acetaldehyde), they have a strong olfactory impact. In addition, the CCs found in wines have a strong affinity for bisulfite and can form stable adducts, which will also interfere in the characteristics of aroma. The greatest challenge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
2
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 30 publications
3
84
2
3
Order By: Relevance
“…Em um processo típico de elaboração de vinhos a faixa de pH é de 3-4, sendo o bissulfito a espécie predominate. 36 (19) Os compostos carbonílicos presentes no vinho reagem com o bissulfito, levando à formação de ácidos alquilsulfônicos, 36 num mecanismo semelhante ao que ocorre em reações na atmosfera envolvendo SO 2 e formaldeído, que resulta na formação de um aduto formaldeído-bissulfito (ácido hidroximetanosulfônico). 37 O acetaldeído também reage rapidamente com o bissulfito, formando o ácido α-hidroxietanossulfônico, não volátil, que diminui a percepção olfativa indesejável do acetaldeído presente no vinho.…”
Section: Figura 7 Estágios Da Fotossíntese: Reações Dependentes Da Lunclassified
See 1 more Smart Citation
“…Em um processo típico de elaboração de vinhos a faixa de pH é de 3-4, sendo o bissulfito a espécie predominate. 36 (19) Os compostos carbonílicos presentes no vinho reagem com o bissulfito, levando à formação de ácidos alquilsulfônicos, 36 num mecanismo semelhante ao que ocorre em reações na atmosfera envolvendo SO 2 e formaldeído, que resulta na formação de um aduto formaldeído-bissulfito (ácido hidroximetanosulfônico). 37 O acetaldeído também reage rapidamente com o bissulfito, formando o ácido α-hidroxietanossulfônico, não volátil, que diminui a percepção olfativa indesejável do acetaldeído presente no vinho.…”
Section: Figura 7 Estágios Da Fotossíntese: Reações Dependentes Da Lunclassified
“…37 O acetaldeído também reage rapidamente com o bissulfito, formando o ácido α-hidroxietanossulfônico, não volátil, que diminui a percepção olfativa indesejável do acetaldeído presente no vinho. 36 …”
Section: Figura 7 Estágios Da Fotossíntese: Reações Dependentes Da Lunclassified
“…For example, glyceraldehyde forms stable hydroxysulfonate adduct, which could contribute to the mechanism of the inhibition of Maillard browning by sulfite species (Keller et al, 1999). Dissociation constants of carbonyl bisulfite compounds at pH 3.5 have been reported by Azevedo et al, (2007). They revealed that aliphatic aldehydes form adducts with S (IV), whereas ketones, cyclic aldehydes, and trans-alkenes interact weakly and are found predominantly in the free form.…”
Section: Formation Of Adducts With Carbonyl Compoundsmentioning
confidence: 99%
“…O conhecimento sobre as concentrações dos ácidos hidroximetanossulfônico (AHMS) e α-hidroxietanossulfônico (AHES) e dos demais ácidos hidroxialquilssulfônicos (AHAS) formados com compostos carbonílicos de cadeias mais longas é fundamental para entender o equilíbrio entre os CC na forma livre e na forma de aduto (AHAS), e como essas espécies influenciam na qualidade sensorial de vinhos ou de outras bebidas fermentadas 69 .…”
Section: Moléculas Que Se Combinam Com O Sounclassified